(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this era of industrial revolution (IR 4.0), coupled with the emergence of the deadly global pandemic of COVID-19, organizations are compelled to embrace new strategies for their routine decision-making. Innovation is the core of organization policy and the lifeline of enterprises at the local and global market. There has been a huge amount of research on innovation and elements contributing to innovation performance; however, few of them built a theoretical model to research the correlations among organizational learning, innovation performance, self compassion and organizational performance. Based on the existing studies and literature at home and abroad and considering the development status of innovative enterprises, this paper decomposes organizational learning and organizational performance. The innovation performance play role between organizational learning and organizational performance., organizations can achieve maximum strong excellence and remain in a competitive market.